Sharing Employee: B2B Employment Model in the Era of Coronavirus Disease 2019 and Implication for Human Resource Management - Chen, Zhisheng (Frontiers in Psychology, 2021)
With the explosion of COVID-19, the concept of " Sharing Employees " has emerged in China. This study will discuss the background of the formation of the " Sharing Employees ", how the " Sharing Employees" model is implemented, the relative risks and the impact on human resource management. Currently, this virus is spreading around the world, affecting the economy, and increasing unemployment rate. This study will help other countries to learn from this model and provide suggestions for adopting flexible employment policies to ease employment pressure and increase employment channels through the " Sharing Employees " B2B model.